Pengaruh Konseling Kelompok Dengan Teknik Assertive Training Terhadap Perilaku Membolos Siswa Kelas VIII SMP - Dea, Anartini Pranata (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
This study aims to determine the effect of group counseling services with Assertive Training techniques on students' truancy behavior. This study uses a preexperimental method with a one group pretest-posttest design. The population of the study was grade VIII students who had a habit of truancy, with a sample of 8 students taken using the Purposive Sampling technique. The instruments used were pretest and posttest which had been tested for validity and reliability. The collected data were analyzed using the t-test with a significance level of 0.05. The results of the t-test calculation showed a t-count value of 1.173, while t-table with db N-1 = 7 and a significance level of 0.05 was 0.754. Based on these results, it can be concluded that group counseling services with Assertive Training techniques have a positive and significant effect on reducing students' truancy behavior. These findings are expected to contribute to improving the quality of guidance and counseling services, especially in the application of Assertive Training techniques in schools